Sir John Cornforth AC CBE FRS: his synthetic work. (1st September 2015) - Purchase, Rupert; Hanson, James
Sir John Cornforth's work on the synthesis of cholesterol and penicillamine, on the chemistry of oxazoles, the stereochemistry of the synthesis of alkenes, the synthesis of abscisic acid and of dibenzophospholes as mimics of enzyme action, is reviewed.